Expression of ZNF652, a novel zinc finger protein, in vulvar carcinomas and its relation to prognosis. Issue 1 (27th April 2007) - Holm, R; Knopp, S; Kumar, R; Lee, J; Nesland, J M; Tropè, C; Callen, D F
Abstract : Aims: To determine the levels of expression of ZNF652 and its relevance to prognosis in vulvar squamous cell carcinomas. Methods: 22 cases of vulvar intraepithelial neoplasia (VIN) and tumours from 217 patients with vulvar squamous cell carcinomas were investigated for expression of ZNF652 using immunostaining methods. The effect of ZNF652 ectopic expression was determined in the vulvar carcinoma cell line SW954 by western and cell-based assays. Results: High levels of ZNF652 nuclear expression were observed in 5 (100%) of VIN I, 6 (75%) of VIN II and 109 (50.2%) of the vulvar carcinomas, whereas low levels were seen in 2 (25%) VIN II, 9 (100%) of VIN III and 108 (49.8%) of the vulvar carcinomas. High levels of ZNF652 expression in the vulvar carcinomas were significantly correlated to high expression of EphA2. However, when correcting for multiple testing this correlation was lost. No association was identified between ZNF652 expression and p16, p21, p27, p53, cyclin A, D1, D3, E, EphrinA-1 and human papillomavirus. Variations in levels of ZNF652 were not related to prognosis. Low levels of ZNF652 protein were identified in the vulvar carcinoma cell line SW954. Furthermore, SW954 cells ectopically expressing ZNF652 showed reduced cell proliferation and the ability to form colonies on plastic. Conclusions: ZNF652 protein expression is reduced in 25% of VIN II, 100% of VIN III and approximately 50% of the cases of vulvar squamous cell carcinoma, and may be an early event in the pathogenesis of vulvar squamous cell carcinoma. Variations in the levels of ZNF652 were not related to patient's prognosis.